ANALISIS KOMPARASI PENDAPATAN USAHATANI PADI SAWAH DAN KELAPA SAWIT DI KECAMATAN GERAGAI KABUPATEN TANJUNG JABUNG TIMUR - Trista Purba, Junita; Napitupulu, Dompak; Damayanti, Yusma (Jurnal Ilmiah Sosio-Ekonomika Bisnis, 2019)
This study is aimed to: (1) know the amount of farming costs, revenues and income of rice and oil palm in Geragai Subdistrict, East Tanjung Jabung Regency, and (2) know whether there is any differences in farming costs, revenues and income of wetland rice and oil palm in Geragai District, Tanjung Jabung Timur Regency. This study uses a survey method. Sample is selected by using Cluster Random Sampling method, and the number of samples is determined by using Slovin Method. The study was conducted in Lagan Ulu Village, Geragai District, East Tanjung Jabung Regency. Data were analyzed by using student t-test. The results showed that the costs, revenues, and income between rice farming and oil palm farming differed from one another. The income difference between the two farms is caused by differences in the use of production facilities and labor. The average rice farming income was Rp. 13,695,683 while the average oil palm farming income was Rp. 16,121,672.